Results of multi‐actor collaboration in risk analysis: a simplified risk assessment toolkit for rapid detection of emerging risks - Celine Meerpoel; Biancamaria Ciasca; Nunzia Cito; Antonio Moretti; Sarah De Saeger; Veronica MT Lattanzio (EFSA Journal, 2023)
Abstract The dynamic field of food safety faces continuous challenges, prompting stakeholders to develop collaborative actions for improved food safety systems. As part of these actions, the EU‐FORA fellowship programme was dedicated to a multi‐actor collaboration addressing risks of the unregulated mycotoxins T‐2 and HT‐2 toxins in oats. Critical gaps in risk assessment procedures were identified, leading to a joint effort to develop a strategy for rapid data collection and risk assessment, including the development of a risk assessment toolkit comprising of a training manual and two intuitive Microsoft® Excel files. The toolkit enables efficient data collection and processing, facilitating risk assessment calculations and rapid risk detection. Applying the toolkit to assess T‐2 and HT‐2 toxin risks in Belgian oats revealed minimal concerns, except for children aged 3–9 years, likely due to an overestimation. The toolkit is available on the FoodSafety4EU Platform and will be refined based on user feedback, promoting better risk assessment practices. This approach empowers stakeholders, from professionals to policymakers, fostering collaboration and enhancing food safety practices.